Financial Determinants of Tax Aggressiveness and the Moderating Role of Market Reaction: Evidence from Indonesia's Energy Sector - Sri Sulistyowati; Eva Dewi Kurnia (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the financial determinants of tax aggressiveness and the moderating role of market reaction among energy companies listed on the Indonesia Stock Exchange during 2020–2023. Drawing on agency and political cost theories, it investigates the effects of capital intensity, leverage, profitability, and liquidity on tax aggressiveness, with market reaction (Tobin's Q) as a moderating variable. Panel data from 46 firms (182 firm-year observations) were analysed using quantile regression at Q25, Q50, and Q75. The results show that liquidity consistently reduces tax aggressiveness, whereas capital intensity is significant only among the most aggressive firms. Leverage and profitability have no significant effect. Market reaction moderates the relationships between leverage, liquidity, and tax aggressiveness at the lower and median quantiles, but these effects disappear at the highest quantile. The findings reveal heterogeneous patterns of tax aggressiveness and suggest that market mechanisms alone are insufficient to constrain tax aggressiveness in capital-intensive firms.